Emerging NO2 gas sensing on substitutionally doped Fe on NiWO4 SCES insulators - Lee, Jong Hyun; Kang, Se Hwang; Park, Gi Hyun; Kim, Min Young; Ji, Sanghyun; Choa, Ha Eun; Han, Gi Hyeon; Hwang, Jeong Yun; Lee, Seung Yong; Lee, Kyu Hyoung (Frontiers in Chemistry, 2024)
In this study, we demonstrate the emergence of NO2 gas sensing capabilities in the typically nonactive NiWO4, a strongly correlated electron system (SCES), by introducing substitutional Fe at the Ni site. NiWO4 typically exhibits strong Coulombic repulsion between Ni atoms, resulting in a large band gap of over 3.0 eV and insulating behavior. This correlated behavior is clearly reflected in the significant increase of band gap when considering the Hubbard U correction for the cations, bringing the theoretical value closer to the observed value. The single-phase Fe0.5Ni0.5WO4 displays a notable shift in the [NiO6] symmetric vibration mode and an increase in magnetization. Additionally, theoretical calculations confirm the preservation of the wide band gap, with the Fe and O levels generated within the band gap. These findings indicate that Fe located in Ni sites modulate the Coulombic repulsion in NiWO4 SCES insulators. Unlike the poor gas sensing performance of intrinsic NiWO4, Fe0.5Ni0.5WO4 exhibits a significant NO2 response (Rg/Ra) of 11 at 200°C than other gases and a limit of detection (LOD) of 46.4 ppb. This study provides one pathway into how gas sensing performance can be realized in strongly correlated electron insulators with large band gaps through the introduction of dopant levels at cation sites.